2021
DOI: 10.2166/wh.2021.051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two culture methods for the enumeration of Legionella pneumophila from potable water samples

Abstract: Legionella infections have steadily increased in the United States over the last 20 years, and most of these infections have been attributed to contaminated water. The gold standard for confirmation of Legionella presence in water is culturing with Buffered Charcoal Yeast Extract (BCYE) agar. Following many modifications, this method is still time-consuming, expensive, and can take longer than 10 days for full confirmation. The Legiolert is a newer and simpler culture product that is claimed to be able to quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…This may be why the MPN method produces a small number of false positive samples, which has also been observed in other studies [ 34 , 42 ]. In this study, it was found that the elimination of residual chlorine could effectively improve the detection ability of L. pneumophila by the MPN method, which was consistent with the opinion of a reported article [ 35 ], because chlorine residues decrease the culturability of L. pneumophila .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be why the MPN method produces a small number of false positive samples, which has also been observed in other studies [ 34 , 42 ]. In this study, it was found that the elimination of residual chlorine could effectively improve the detection ability of L. pneumophila by the MPN method, which was consistent with the opinion of a reported article [ 35 ], because chlorine residues decrease the culturability of L. pneumophila .…”
Section: Discussionsupporting
confidence: 91%
“…Studies in recent years have indicated that the MPN method is equivalent or better than the plate culture method when used for the determination and evaluation of L. pneumophila in potable water and non-potable water [ 32 ]. Additionally, many studies have disclosed that the MPN method has a higher sensitivity and specificity compared with the plate culture method [ 33 , 34 , 35 , 36 ]. The MPN method has been included in the UK’s Standing Committee of Analysts’ recent update on determining the presence of Legionella , which demonstrates that the MPN method is at least as effective as the plate culture method in detecting and enumerating L. pneumophila in water samples [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stenotrophomonas maltophilia and unidentified organisms were recovered from the false‐positive samples. Several studies indicate that Legiolert and the ISO methods produce comparable results, with Legiolert at times proving to be slightly more sensitive (Boczek et al, 2021; McCuin et al, 2021; Scaturro et al, 2020; Spies et al, 2018). In this study, the counts were close to the limit of detection for both methods, and with such few positives, determining whether one method truly offered an advantage in sensitivity of detection was not possible in this study.…”
Section: Resultsmentioning
confidence: 99%
“…L. pneumophila was quantified using the Legiolert most probable number assay (IDEXX Laboratories, Inc., Westbrook, ME, USA) according to manufacturer protocols [IDEXX]. Legiolert is a liquid-based culture most probable number (MPN) method that correlates well with standard culture methods and has a low (3–4%) false positivity rate [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%